2019
DOI: 10.1111/tid.13034
|View full text |Cite
|
Sign up to set email alerts
|

A case of pan‐resistant Burkholderia cepacia complex bacteremic pneumonia, after lung transplantation treated with a targeted combination therapy

Abstract: We describe a case of one patient with cystic fibrosis who developed a pan‐resistant Burkholderia cepacia complex rapidly progressive bacteraemic pneunonia, following bilateral lung transplantation. The patient was treated with a targeted combination antibiotic therapy (meropenem plus ceftazidime/avibactam plus high doses of nebulized colistimethate sodium). Evolution of the disease was complicated by multiple organ system dysfunction. Finally, clinical improvement and microbiological cure was achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 13 publications
0
9
0
2
Order By: Relevance
“…However, alternative decolonization strategies are emerging in the perioperative period of a LTx. Indeed, different solutions have been tested with interesting results, such as perioperative tracheobronchial lavage and/or pleural irrigation with antiseptic solutions [34,35] or a combination of antibiotic therapies [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…However, alternative decolonization strategies are emerging in the perioperative period of a LTx. Indeed, different solutions have been tested with interesting results, such as perioperative tracheobronchial lavage and/or pleural irrigation with antiseptic solutions [34,35] or a combination of antibiotic therapies [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports described the favorable clinical response to a CAZ-AVI-containing regimen in the treatment of infections caused by B. cepacia complex. These include one case report in a 2-month-old infant with B. cepacia bacteremia (99) and several cases of lung transplant and cystic fibrosis patients with B. cepacia serious infections (100)(101)(102)(103)(104). In an in vitro study, CAZ-AVI was demonstrated to have greater activity specifically against Burkholderia multivorans than ceftazidime (MIC 90 values of 4 and 16 mg/liter, respectively).…”
Section: Clinical Datamentioning
confidence: 99%
“…Among these combinations, colistin and ceftazidime-avibactam with or without ceftolozane-tazobactam have been reported successful for BCC even with disseminated disease. 69,[93][94][95] The rationale for using avibactam is that it restores susceptibility to ceftazidime for BCC isolates. 96 Precise surgical techniques have been described especially for B. cenocepacia and include irrigation of the chest cavity and bronchi with 0.5% povidone-iodine solution or taurolidine.…”
Section: Pseudomonas and Burkholderia: Therapeutic Optionsmentioning
confidence: 99%
“…They include such diverse options as bilateral pneumonectomy and ECMO pre-LTX in a patient with sepsis, a study of antibiotic perfusion of explanted lungs in a porcine model and less common antibiotic combinations based on in vitro studies of multiple antibiotic bactericidal testing, and last but not least, bacteriophage therapy which seems to hold a degree of promise. 93,94,96,[98][99][100][101][102][103][104][105] As mentioned earlier, a systematic approach has recently been described but is yet to be validated and widely adopted. 8 Pseudomonas and Burkholderia: Lung Transplant Outcomes-Morbidity, Mortality, Societal Cost Single lung transplantation (SLTx) allows the study of the differences between native and allograft lungs.…”
Section: Pseudomonas and Burkholderia: Therapeutic Optionsmentioning
confidence: 99%